2022
DOI: 10.1371/journal.pone.0268971
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of exit-knowledge of ambulatory patients on their dispensed medications: The case in the outpatient pharmacy of Mizan-Tepi University Teaching Hospital, Southwest Ethiopia

Abstract: Background Patient’s knowledge about dispensed medications is one of the major factors that determine the rational use of medicines. Objectives This study aimed to assess exit-knowledge of ambulatory patients about their dispensed medications and associated factors at the outpatient pharmacy of Mizan-Tepi University Teaching Hospital, Southwest Ethiopia. Methods A hospital-based cross-sectional study design was conducted from August to October 2021. Study subjects were selected by random sampling technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…However, most of the patients who had poor knowledge of their medication were the illiterate and those whose perceived language wasn't clear. These results are in line with those of a similar study (Peacock, 2022), which found that out of the 400 participants, 116 (29.0%) participants had sufficient exit knowledge about their dispensed medication. Patients with higher education level had increased exit-knowledge of dispensed medications than those with no formal education.…”
Section: Level Of Patients' Knowledgesupporting
confidence: 92%
“…However, most of the patients who had poor knowledge of their medication were the illiterate and those whose perceived language wasn't clear. These results are in line with those of a similar study (Peacock, 2022), which found that out of the 400 participants, 116 (29.0%) participants had sufficient exit knowledge about their dispensed medication. Patients with higher education level had increased exit-knowledge of dispensed medications than those with no formal education.…”
Section: Level Of Patients' Knowledgesupporting
confidence: 92%